A framework to enforce anti-predation rules - Kai Hüschelrath; Jürgen Weigand (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
The paper develops a framework to enforce anti-predation rules that explicitly takes the intervention stage into account. In particular, it is proposed to improve predation enforcement by focusing on two channels: refining the current regime, and amending it. With respect to the refinement of the current predation enforcement regime, criteria for the imposition of optimal gain- or harm-based fines are derived in order to sharpen the deterrent effect of predation enforcement. However, given the very low probability of conviction for predators a policy proposal solely based on an increase in the fines for detected and convicted predators might be too weak to significantly amplify the deterrence effect in particular and to improve predation enforcement in general. As a consequence, the introduction of a pre-screening approach is proposed, which aims at identifying industries in which entry is difficult but desirable and a predation strategy might be a suitable instrument for an incumbent to fight such occasional entry attempts. In those industries, it is advisable to reduce the high standard of proof in predation enforcement, as its basic justification - the danger to create a negative deterrence effect - is significantly reduced.
Keywords: K21; L41; 330; Competition policy; monopolisation; predation; enforcement; sanctions; screening; Verdrängungswettbewerb; Wettbewerbspolitik; Wettbewerbsaufsicht; Rechtsdurchsetzung